1997
DOI: 10.1111/j.1439-037x.1997.tb00518.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Okra Planting Density and Spatial Arrangement in Intercrop with Maize on the Growth and Yield of the Component Species

Abstract: The effects of three okra planting densities (28 000; 56 000 and 111 000 plants ha') intercropped within or between maize rows were investigated in two field trials during the 1990 and 1991 wet seasons at Nsukka. The plant height and the leaf area index (LAI) increased as the planting density increased in sole or intercropped okra while the number of branches per plant decreased with increasing okra planting density. The height of maize plants also increased as okra planting density increased but the LAI decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 8 publications
2
17
0
1
Order By: Relevance
“…Seed yield of the three varieties of common bean in intercropping generally exhibited an extreme decline as their planting was delayed after maize, which implies the presence of severe competition for resource as maize crop becomes well established. In previous studies, maize has been shown to be a great competitor in mixtures and had the advantage of being taller than cowpea and might intercept more light than cowpea [18]. Competition for nutrients can also result in substantial crop yield reductions in mixed cropping systems [19].…”
Section: Growth Parametermentioning
confidence: 99%
“…Seed yield of the three varieties of common bean in intercropping generally exhibited an extreme decline as their planting was delayed after maize, which implies the presence of severe competition for resource as maize crop becomes well established. In previous studies, maize has been shown to be a great competitor in mixtures and had the advantage of being taller than cowpea and might intercept more light than cowpea [18]. Competition for nutrients can also result in substantial crop yield reductions in mixed cropping systems [19].…”
Section: Growth Parametermentioning
confidence: 99%
“…Agboola and Fayemi (2001) investigated maize/Mucuna pruriens intercrop and observed that maize yield was reduced but intercropping with Calopogonium mucunoides, groundnut, pigeon peas did not affect the maize yield, their studies equally indicated that C. mucunoides, groundnut, pigeon pea and cowpea fixed 370 kg N/ha when intercropped with maize. Maize-potato intercropping performed better than the sole potato as was observed by Begum et al (1999) and in maize-okra intercropping Muoneke and Asiegbu (1997) observed that yield and yield components of okra was increased. Sharma and Tiwani (1996) reported that maize/tomato intercrop increased the number and weight of fruit.…”
Section: Contributions Of Intercropping To the Soil Growth And Yieldmentioning
confidence: 51%
“…Muoneke et al (2001) reported yield reduction in Roselle/cowpea intercrop and the reduction was the highest when intercropped with Roselle planting density of 37,000 Roselle plant/ha. The authors attributed yield reduction to competition for growth resources as reported in other crops in mixtures by other various workers (Willey, 1979;Muoneke and Asiegbu, 1997). Ikeh et al (2013) noted yield increase in water yam/vegetable cowpea.…”
Section: Contributions Of Intercropping To the Soil Growth And Yieldmentioning
confidence: 85%
“…Okigbo and Greenland (1998) reported that farmers in Africa practice intercropping because it gives higher growth performance, higher vegetative growth and higher total yields and greater returns than the same crop grown under monocropping system. Growing okra plant under sole cropping condition lead to serious defoliation and subsequent yield reduction (Theunisseu, 1994, Muoneke andAsiegbu, 1997;Broad, 2007, Banfu andMochiah, 2011). Okra leaves damage caused by the flea beetles reduced the photosynthetic capacity of leaves which was manifested in the lower plant heights, number of fruit/plant, light fresh fruit weights and lower fruit yield obtained from sole okra planted plots that suffered more insect damage ( Adelana, 1986 .…”
Section: Discussionmentioning
confidence: 99%